Budaya Badati Sebagai Identitas Nasional Masyarakat Kepulauan Banda - Syarifudin (Universitas Banda Naira, 2024)
This study investigates a community tradition in welcoming Indonesian independence in Banda Naira, Central Maluku. This study found two main problems: 1) How the independence ceremony was carried out; and 2) How the unity of heritage and modern religions contributed to Indonesian independence. To describe the independence ceremonies of modern religions and heritage religions, a qualitative descriptive approach is used. As research objects, in-depth discussions, interviews, and analysis of oral literature are data collection methods. This study involved seven informants from heritage religions and seven informants from modern religions. Haberman's concept is used in data analysis, which begins with data collection, organising it, analysing and interpreting it, and drawing conclusions. The results of the research show that the independence ceremony of the Republic of Indonesia is practiced in Badati culture as a means of reinforcing brotherhood as the identity of the Indonesian nation in Banda Neira. This research describes various aspects of independence rituals, both internal and external, in communities that adhere to the teachings of modern religions and inherited religions. This condition has an impact on the Badati social and cultural order as the basis for maintaining local solidarity, local wisdom, and local wisdom as the cultural identity of the people in Banda Neira. Badati culture is a typical expression for the Bandanese people in welcoming Indonesian independence, which produces social harmony to achieve true independence